OTTV (SNI 03-6389-2011) and ETTV (BCA 2008) Calculation for Various Building’s Shapes, Orientations, Envelope Building Materials: Comparison and Analysis - Sandra Loekita; Jimmy Priatman (Institute of Research and Community Outreach - Petra Christian University, 2015)
The Indonesian National Standard SNI 03-6389-2000 adapted the 1983 Singapore’s Handbook on Energy Conservation and limited the Overall Thermal Transfer Value (OTTV) of the building envelope to 45 Watt/m2. In 2008, the Singapore’s Building and Construction Authority (BCA) shifted to Envelope Thermal Transfer Value (ETTV) value of 50 Watt/m2, while SNI 03-6389-2011 continues to use OTTV. This paper reviewed the new SNI 03-6389-2011 and compared it with BCA by calculating OTTV and ETTV of prismatic buildings with eight different shapes and building orientations, 11 Window to Wall Ratio, and 27 building envelope materials. This study also tested those variables to find the best building shape and orientation for an energy saver building. The result shows that ETTV (BCA) is stricter than OTTV (SNI 03-6389-2011) except the OTTV with black building envelope, while parallelogram shape building with North-South orientation is the best combination of energy saver building.